Effect of a Phytase Product on Protein and Phosphorus Digestibility in Shrimp Litopenaeus Vannamei Fed an Air Classified Pea Protein Flour (Ppf) Based Diet - Newkirk, Rex; Ricque-Marie, Denis; Cruz-Suarez, L. Elizabeth; Zavala-Chavez, Brenda M.; Nieto-Lopez, Martha; Guajardo, Claudio; Tapia-Salazar, Mireya; McCallum, Ian M. (Avances en Nutrición Acuicola, 2019)
Air classification provides an economical method for separating the lower density protein fraction in finely ground pea to manufacture pea protein flour (PPF) suitable for aquafeeds, but in this process phytate (inositol hexaphosphate) is also concentrated. The phytate phosphorus, which can not be digested by shrimp such as L.vannamei for lack of phytase enzyme activity, becomes a pollutant in the aquatic environment. Phytate is also considered to be an antinutritional factor in fish nutrition for forming complexes with amino acids, depressing digestive enzyme activity and decreasing digestibility of proteins. The objective of this study was to measure the effect of a commercial phytase enzyme (Allzyme) on the apparent dry matter digestibility, crude protein digestibility and phosphorus digestibility in Pacific white shrimp Litopenaeus vannamei, fed a practical diet containing 40% PPF, the source of phytate bound phosphorus. Apparent dry matter digestibility (ADMD), apparent protein digestibility (APD), and apparent phosphorus digestibility (APhosD) of air classified pea protein flour, with and without phytase, was determined in test diets where PPF replaced 40% of the complete formula of a reference diet (RD). The phytate free RD was formulated to meet the minimum nutrient requirements of shrimp, except for 87 % of the P requirement, of which 51% was provided by PPF. Chromic oxide was added as an indigestible marker. Phytase, to provide 1000 PU/kg dry diet, was dissolved in water and added to diet 2. The digestibility trial was carried out on 6.3g shrimp that were fed three test diets and one RD for 14 days.